Aplikasi Pengamanan Data Menggunakan Algoritma Steganografi Discrete Cosine Transform dan Kriptografi AES 128 BIT pada SMK PGRI 15 Jakarta - Rika Rahmawati; Dani Rahardjo (Maranatha University Press, 2016)
SMK PGRI 15 Jakarta has a lot of important documents such as financial reports, document collaboration and other important papers. Document security is still not done correctly so that the stored information is still very vulnerable to unknown, retrieved and manipulated by parties who are not entitled to that information. One way that information safe is to use steganography techniques. So the objective of this thesis is to build desktop-based applications to secure the data (information) in order to be secret by inserting secret messages that have been encrypted in the form of an image file. Steganography algorithm used is DCT (Discrete Cosine Transform). Data that has been inserted into the previous image is already in encrypted with 128 bit AES algorithm, so that data confidentiality is guaranteed. Based on the results of experiments conducted in this study, File Embedded processors who do have an average completion time of 432.3 seconds, and managed to get a good quality Steganography with the average value of the relatively small MSE of 1.38 dB and flat -rata PSNR of 47.66 dB. While the process Extract Files that do have an average completion time of 139,6detik, as well as the success rate of 100%. By using Steganography DCT (Discrete Cosine Transform) and Cryptographic techniques AES (Advanced Encryption Standard) 128 bit is very helpful in maintaining the confidentiality of documents that are not easily read by people who are not entitled to the document. So the security issues faced by SMK PGRI 15 Jakarta can be resolved.